Facilitated transport membranes by incorporating different divalent metal ions as CO2 carriers. Issue 69 (11th July 2016) - Peng, Dongdong; Liu, Ye; Wang, Shaofei; Tian, Zhizhang; Xin, Qingping; Wu, Hong; Chen, Jianfeng; Jiang, Zhongyi
Abstract : The comparison on CO2 separation performance of facilitated transport membranes by introducing different divalent metal ions is reported. Abstract : Facilitated transport membranes by utilizing π complexation reactions between metal ions and penetrants have been actively explored, however, the different facilitated transport abilities of metal ions remains to be disclosed. In this study, poly( N -vinylimidazole) coated carbon nanotube particles (PVI@CNT) were prepared via precipitation polymerization of N -vinylimidazole monomers on a CNT surface. The PVI@CNT particles were then loaded with four kinds of divalent metal ions, Cu 2+, Fe 2+, Ca 2+ and Mg 2+, and incorporated into polyimide (PI) to prepare M 2+ –PVI@CNT hybrid membranes. The structure of M 2+ –PVI@CNT particles and PI–M 2+ –PVI@CNT membranes was analyzed by different characterization tools. Taking CO2 /CH4 as the model separation system, the hybrid membranes containing Cu 2+ and Fe 2+ at filler content of 7 wt% showed the maximum increase of CO2 permeability of 89% and 87% compared with those of a pristine PI membrane. Meanwhile, the selectivity of these membranes shows little increase. However, membranes containing Ca 2+ and Mg 2+ show only little enhancement in the separation properties. Such results can be interpreted based on the π complexation mechanism, transition metal ions Cu 2+ and Fe 2+ possess a strong CO2 facilitated transport ability whereas main-group metal ions Ca 2+ and Mg 2+ possess a weak facilitated transport ability. Finally, a correlation of the electronegativity of metal ions with their CO2 facilitated transport abilities was explored.